DESAIN SEPATU PRIA DENGAN ORNAMEN GUNUNGAN WAYANG MENGGUNAKAN TEKNIK LASER GRAFIR UNTUK MENINGKATKAN KREATIFITAS DAN EKONOMI PADA PENGRAJIN SEPATU DI SIDOARJO - Choirul Anam (Fakultas Ekonomi Universitas 45 Surabaya, 2017)
With the increasing socialization programs to appreciate domestic products and to awaken public awareness of the value of local wisdom so that it may become an opportunity for creative people to combine their products especially shoes, added with local cultural values to support cultural preservation programs, one of them Is the Wayang Gunungan. This research was conducted to identify the value of Wayang Gunungan culture when included into product design, especially men's shoes and to understand the process of making shoe products with cultural elements included, using modern technology which is laser. Through this research, the identification of values is done by using the theory of cultural studies to obtain the result of applying Wayang Gunungan as well as experimentation and development of shoes during the production process using laser technology. The results of this research indicates that the value of the Wayang Gunungan can be identified and applied to the shoe product and then continued with the production process of several shoe models themed Wayang Gunungan and become shoes with different characteristics. Further research needs to be done to reinforce and deepen theories used and the shoe results that are made would potentially be a reference in combining other cultural values to preserve local wisdom on the design of shoes.